Calcium and Magnesium Variations in Grasses under Natural Forests of Chir Pine (Pinus roxburghii) at Different Aspects in Mid Hills of Himachal Pradesh - Guleria, Vipan; Nayital, R.K.; Gupta, B. (Indian Journal of Agroforestry, 2020)
The study was conducted at Solan in District Solan of Himachal Pradesh at an altitude of 1300 m above msl. Maximum calcium contents of above ground grass biomass were found to be 0.56 and 0.64 per cent. Chir pine forest and open grassland whereas magnesium recorded maximum value of 0.69 and 0.85 per cent under Chir pine and open grassland, respectively. Calcium recorded decreasing trend whereas magnesium recorded increasing trend with advancement of growth. Below ground biomass of grasses recorded less percentage of calcium and magnesium contents under Chir pine and open grassland than above ground grass biomass at all the aspects. Overall there was no significant influence of aspects as far as calcium and magnesium contents are concerned.